Território e trajetórias de subalternidade em uma cidade média: um olhar sobre o processo de urbanização de Mossoró(RN) - Queiroz, Rodrigo José de Gois (2018)
This thesis sought to analyze the subalterns trajectories in the production of the territory of the city of Mossoró (RN) from the point of view of the sertanejos subjects. The main objective of this investigation is to understand the process of production of the territories precariously included in Mossoró city. It’s relations of domination and appropriation, where we give a focus on the backland memory and the process of resistance and construction of the dry identity. In the first part, we present a context for the understanding of Mossoró as a intermediary city. In the first chapter, we highlight the economic flows and their consolidation in the northeastern urban network, while we present a historical recovery of the city's production in terms of housing. The process of occupation of the city by the waves of sertanejo escapers producing the informal city gained prominence. In the great drought of 1877, the city, which had about 4,000 inhabitants in 1878, receives about 32,000 escapers, other sources speak of more than 40,000 escapers, who roam the streets of the city, with the formation of the concentration camp of the 'Alto do Pão Doce', where most of the population died of illness. In the second chapter, we make a theoretical research about the meanig of informal city and the the slums development process. Furthermore we present data about this process in the city of Mossoró through qualitative interviews. In the second part, we debate about method and methodology through extensive bibliographic research, in which we propose a reflection on the dialectical method and the socio-spatial dialectic, bringing to light the contributions of the critic of everyday life in Lefebvre for an approximation with the socio-spatial reality. This debate leads to an appreciation of the dimension of experience within the scope of critical Geography, culminating in the possibilities of qualitative research. In the third part, we present reflections on decolonial thinking and the perspective of subaltern subjects in the production of the territory. The relational reading of geographic theory is fundamental for understanding the tension between the dimensions of domination and appropriation in territorial production. It emphasizes the power relations in the context of social conflicts. The concept of coloniality of power is of great importance for the comprehension of the Brazilian socio-economic formation in the contemporary moment, since it opens the possibilities for the understanding that the colonial domination relations were molding to the different political contexts, remaining until today. In the fourth chapter, we focus on understanding the socio-spatial formation of the sertões of Northeast Brazil, presenting the point of view of vanquished in their social struggles. We intend to rescue the fighting memory of the subaltern sertanejo subjects, highlighting their spontaneous actions and organized against the uneven production of the territory on several fronts, such as the construction of the sertaneja utopia in Canudos city. In the fifth chapter, we present the occupation process of the hinterlands of Rio Grande Norte, highlighting the marks of oligarchies and coronelismo, especially of the latifundium, always seeking to give visibility to the point of view of vanquished. We also do a survey for the droughts of the twentieth century, through the newspaper clippings, where we highlight actions of looting during the 1990s, a period in which the slum process had a great growth in the city. For the 21st century, we bring elements of the actions of subaltern subjects and the permanence of socio-spatial inequalities. In addition, we have identified the role of the latifundia since the colonization process within the sertaneja socio-spatial formation, as one of the assumptions of socio-spatial inequalities, which reverberates in the urban world of the city of Mossoró today.